Preschool Teacher’s Performance Evaluation System - Yusop, Nor Iadah; Yao, Goh Fang; Saip, Mohamed Ali; Mohd Nor, Adiyati (Multidisciplinary Applied Research and Innovation, 2023)
Kindergartens are important educational settings for the methodical instruction of children as well as the dissemination of information and culture. In a kindergarten setting, the teachers can do this well as they have the most contact and familiarity with the kids. Their roles are crucial to ensuring a child's academic achievement throughout their school years, hence kindergarten administration should always keep an eye on their performance. Nevertheless, in recent years a formal checklist has been used to evaluate preschool teachers. As a result, the management of the kindergarten does not maintain regular and consistent instructor records. Additionally, this manual method needs a lot of effort, time, and resources. To overcome these problems, a web-based follow-up system for evaluating and monitoring the performance of teachers was developed. Teachers’ key performance indices (KPI) which are defined by the kindergarten’s management serve as the basis for the system. The waterfall method was employed to guide the system development process. The database is managed using phpMyAdmin, a PHP and MySQL administration tool. The system allows the kindergarten's administration to monitor the performance of its teachers, and the teachers themselves will become aware of their own performance.